Obstetrical Risk Factors for Neonatal Malaria in The Democratic Republic of Congo - Singh, Megan; Doshi, Sejal; Hangi, Stan; Bartels, Susan (Global Health: Annual Review, 2019)
Neonates in the Democratic Republic of Congo are challenged by a low resource health care system and endemic malaria. Current practices to reduce malaria rates involve widespread blood smear testing and administration of antimalarials to febrile infants. However, the ongoing threat of resistance and associated cost indicate the need for targeted guidelines on malaria treatment amongst neonates. The present study investigates obstetrical risk factors for neonatal malaria in order to guide current practices. Factors investigated included febrile illness, hypertension, premature rupture of membranes (PROM), urinary tract infections, placental complications and diabetes during pregnancy and their association with neonatal malaria. Chi-squared analysis and odds ratio with a 95% CI revealed that PROM had a significant association with neonatal malaria.